Perbedaan Latihan Drive Arah Tetap dan Arah Berubah terhadap Kemampuan Melakukan Rally 3 Menit pada Petenis Putra Klub Diklat Semarang Tahun 2009 - Husni Fahritsani (utile: Jurnal Kependidikan, 2018)
The purpose of this study to determine the difference between the exercise drive towards fixed and direction changes with the ability to rally 3 minutes in tennis men's club training semarang 2009 and better between workouts drive towards fixed and the direction changed for the ability to rally 3 minutes at tennis player 's son semarang training club in 2009. The population in this study using men's tennis player semarang training club in 2009 as many as 20 people. Samples were taken by using total sampling method of the research conducted by Matched Subject Design (MS). Data obtained from the results were analyzed using t -test formula with short formula and using a significance level of 5 %. Statistical calculations performed on the test results the end of the experimental group and the control group after carrying out an exercise program as much as 16 times the exercise. Statistical calculations derived from the calculated value of 3.161 indicates a value greater than t-table value of 2.262 in the test is based on 5% significance level and degrees of freedom (db) 9. To calculate the mean of the experimental group was 22.6 and the mean calculation of the control group is 21.5. The conclusion from this study is there is a distinct difference between the exercise drive towards fixed and the direction of change in the ability of men's tennis rally 3 minutes Semarang training club in 2009. And between workouts drive direction anyway better than exercise drive direction change with the ability to rally 3 minutes at tennis training clubs semarang son . The author suggests in providing training forehand and backhand drive on the son of the club's players semarang training exercise in 2009 in order to use the drive towards fixed.